Hoarding Disorder A Comprehensive Clinical Guide. - Rodriguez, Carolyn I. (American Psychiatric Association Publishing, 2022)
"Accounts of hoarding behaviors stretch back thousands of years-most recently depicted in popular reality television series-but it wasn't until the publication of DSM-5 in 2013 that hoarding was classified as a disorder in its own right rather than as a symptom of obsessive-compulsive disorder or obsessive-compulsive personality disorder. In this single source, readers can access the most up-to-date comprehensive information on what is known about the disorder. Drawing on both the authors' own clinical experience and published research, Hoarding Disorder: A Comprehensive Clinical Guide examines the phenomenology and etiology of the disorder, as well as psychotherapeutic and pharmacological treatments, challenges, and future directions. Appendixes feature useful symptom rating scales that can be applied to practice. Whether readers are practicing psychiatrists, psychologists, or other mental health professionals; professionals in training; or peer support counselors and community advocates; all will benefit from the wealth of information in this volume-made more easily accessible through key points in each chapter-and find the guidance they need to effectively and compassionately treat patients with hoarding disorder"--